A dynamic capabilities view of employability: Exploring the drivers of competitive advantage for university graduates. Issue 1 (11th January 2016) - Finch, David J; Peacock, Melanie; Levallet, Nadege; Foster, William
Abstract : Purpose: – The increasing demand for post-secondary education, and the ongoing difficulty students' face in securing appropriate work upon program completion, highlight the importance of an enhanced understanding of employability resources for university graduates. Just as organizations achieve a strategic advantage from resources and dynamic capabilities (DCs), university graduates can similarly apply these principles and tactics to be competitive in the job market. The purpose of this paper is to ask the question: how can new graduates enhance their competitive advantage when entering the employment market? To address this question the authors propose to adopt the DCs framework to analyze the competitive advantage of a graduate and argue that university graduates can take specific steps to enhance their own competitive advantage in the labor market. Design/methodology/approach: – An extensive review of the existing human resource and strategic management literature was used to develop a conceptual DCs model of employability. The core dimensions of the conceptual model were refined using 26 one-on-one interviews with employers of new university graduates. This study concludes by recommending specific empirical and experimental research to further test the model. Findings: – The results from the qualitative study identified the importance of four specific resources that university graduates should possess: intellectual, personality, meta-skill and job-specific. In addition, the authors suggest that integrated DCs are crucial for enhancing the value of these individual resources. Both pre-graduate application and the construction of personal narratives are essential signals that university graduates can mobilize individual resources in a complementary and strategic manner, in real-world settings, to maximize value. Research limitations/implications: – This is an exploratory study and is designed as a foundation for future empirical and experiential research. Practical implications: – The findings suggest that, in order to increase employability, university students need to assume a DCs view of competitive advantage. As a result, students need to reflect on both their intrinsic and learned resources to create a systematic competitive advantage that is valued, rare and difficult to replicate or substitute. Social implications: – This paper challenges students to assume a holistic view of education by recognizing education extends far beyond a classroom. Therefore, differentiation and value creation is reflected in the synthesis and application of both intrinsic and learned resources. Originality/value: – The integration of strategic management and human resource literature is a unique theoretical approach to explore the drivers of graduate employability.